«Rossica» - the concept evolution at the Russian bibliology in the XIX-XXI centuries - I. S. Troyak (Библиосфера)
The article represents main approaches to definition of the concept «Rossica» at the Russian bibliography and bibliology based on the domestic publications analysis of two last decades. The term ambiguity related to its national or thematic segments is noted. The attention is paid to using Rossica materials in historical researches, as well as prospects of studying this category of editions.